2019
DOI: 10.21608/epsj.2019.34542
|View full text |Cite
|
Sign up to set email alerts
|

Acidification of Broiler Feeds in Relation to Bone Chemical and Biophysical Traits

Abstract: A number of 150 one-day old Arbor Acres broiler chicks, was used to examine effects of supplementing diets, with sodium formate, formic acid, probiotics or probiotics-enzymes mix, on growth performance, some blood parameters, tibia chemical composition, and biophysical traits. Birds were distributed into 5 groups; each group was subdivided into 3 replicates of 10 chicks. Birds of control group (T1) were fed basal diets with no supplements, while birds of other groups, were fed basal diets supplemented with 2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…In this study, there was no discernible difference between the binder fed group and the control group for the serum indices ALP, AST, and ALT, though there was a slight increase in these values. T. Abdelaziz et al (2015) had reported that there were no significant differences in the values of AST, ALT, and ALP when compared with the control in their study with antimycotoxins. The workers reported that the use of a natural anti-mycotoxin (toxin binders) improved liver activities without any negative effects.…”
Section: Serum Biochemical Indices Of Broiler Finisher Chickens Fed D...mentioning
confidence: 91%
“…In this study, there was no discernible difference between the binder fed group and the control group for the serum indices ALP, AST, and ALT, though there was a slight increase in these values. T. Abdelaziz et al (2015) had reported that there were no significant differences in the values of AST, ALT, and ALP when compared with the control in their study with antimycotoxins. The workers reported that the use of a natural anti-mycotoxin (toxin binders) improved liver activities without any negative effects.…”
Section: Serum Biochemical Indices Of Broiler Finisher Chickens Fed D...mentioning
confidence: 91%